Hepatic Dysfunction in Patients Receiving Intravenous Amiodarone. Issue 2 (February 2016) - Hashmi, Ali; Keswani, Nicole R.; Kim, Sharon; Graham, David Y.
Abstract : Objectives: Amiodarone is a commonly used antiarrhythmic drug. Hepatotoxicity following chronic oral administration occurs in 1% to 3% of patients. Hepatotoxicity following intravenous (IV) administration is infrequent but may be associated with dramatic increases in serum transaminases. We describe the incidence of liver toxicity among patients receiving IV amiodarone during a 5-year period. Methods: This was a single-center retrospective review of patients receiving IV amiodarone for any cause. The outcome measures were development of elevated serum transaminases and the relation of transaminitis to all-cause 30-day mortality. Results: A total of 1510 patients received amiodarone intravenously between 2005 and 2011; 77 (5%) developed elevated liver enzymes. Enzyme elevation was divided into mild (100–300 IU/L), moderate (300–1000 IU/L), and severe (>1000 IU/L). The median alanine aminotransferase was 189 (37–10, 006) IU/L and aspartate aminotransferase was 253 (84–12, 005) IU/L. The 30-day mortality among those with transaminitis was 22%; however, no patient died of amiodarone-related liver disease. Conclusions: Amiodarone can cause severe elevation in liver enzymes. The incidence of severe transaminitis is low; deaths following IV amiodarone are rarely caused by drug-induced liver failure. Abstract : Hepatotoxicity following intravenous amiodarone administration may result in dramatic increases in serum transaminases. The authors performed a single-center retrospective review of 1510 patients receiving intravenous amiodarone for any cause during a 5-year period. The outcome measures were development of elevated serum transaminases and the relation of transaminitis to all-cause 30-day mortality. Although amiodarone can cause severe elevation in liver enzymes, the incidence of severe transaminitis is low; deaths following intravenous amiodarone rarely are caused by drug-induced liver failure.